PERANCANGAN KARAKTER MASKOT RISHII SESUAI KEPRIBADIAN BRAND GURI RAMEN - Maria Regina Taufik; Shienny Megawati; Evan Raditya (Jurnal Dimensi DKV Seni Rupa dan Desain, 2023)
The Rishii Mascot Character Design According to the Guri Ramen Brand Personality. Guri Ramen is the first halal ramen restaurant in Surabaya with the USP (Unique Selling Proposition) of Sapporo-style ramen. Guri Ramen wants to present a mascot to assist promotional activities and increase awareness of the target market. The purpose of this research is to design the Rishii mascot character which will be used to strengthen the brand image and promote Guri Ramen. This research was conducted using qualitative methods and literature studies. The literature study was conducted to find information regarding the design and use of mascots in promoting a brand. The design process begins with analyzing the brand, competitor research, and USP analysis using the Value Proposition Canvas, and finally finding the personality of the Guri Ramen brand. The result of this design is a character named Rishii which is a visualization of the personality of the Guri Ramen brand, which is then applied to various promotional media for the brand. Keywords: character design, mascot, USP, brand personality, promotion media